Analysis of Critical Thinking Skills High School Students in the District of Semarang Material Environmental Change Curriculum 2013 - Setianingsih, Rizki; Marianti, Aditya; Ngabekti, Sri (FMIPA UNNES, 2019)
Learning science at school is expected to develop critical thinking skills students for the challenges of the 21st century. Ccritical thinking skills are integrated in the curriculum of 2013. The ability of high scientific literacy show high critical thinking skills. This study aimed to analyze the level of critical thinking skills of high school students in the District of Semarang on environmental changes material of curriculum 2013. This study was descriptive quantitative survey method using a questionnaire and observation sheet. The research was conducted in three high schools in Semarang District selected by purposive sampling in SMAN 1 Ungaran, SMAN 1 Bergas and SMA Islam Sudirman Ambarawa. Respondents used is class X IPA as many as 195 students in three schools. The data were analyzed using R software. Based on the results of research, critical thinking skills of students only in the quite critical category . Kruskal-Wallis test results of chi-square showed a difference in the level of critical thinking skills of students at SMAN 1 Ungaran, SMAN 1 Bergas and SMA Islam Sudirman Ambarawa with significant value 0.000009439. The highest level of high schools students critical thinking skills based on average indicators of critical thinking is SMAN 1 Ungaran with a percentage of 58%. The percentage of students' critical thinking skills in SMAN 1 Bergas and SMA Islam Sudirman Ambarawa is 57% and 55%. Critical thinking skills of students at SMAN 1 Ungaran, SMAN 1 Bergas and SMA Islam Sudirman Ambarawa included in the quite critical category. The proportion of students at the level of critical thinking skills in SMAN 1 Ungaran, SMAN 1 Bergas and SMA Islam Sudirman Ambarawa is different. The questionnaire results and students' test results showed linkage relationships based on Pearson correlation analysis chi-square obtained 42.199 squared count> squared table with significant value 0.000000168.